Body mass index and clinical outcomes in patients with intracerebral haemorrhage: results from the China Stroke Center Alliance - Yongjun Wang; Zixiao Li; Xingquan Zhao; Hongqiu Gu; Zhentang Cao; Xinmin Liu; Yingyu Jiang (Stroke and Vascular Neurology, 2021)
Background and aim Obesity paradox has aroused increasing concern in recent years. However, impact of obesity on outcomes in intracerebral haemorrhage (ICH) remains unclear. This study aimed to evaluate association of body mass index (BMI) with in-hospital mortality, complications and discharge disposition in ICH.Methods Data were from 85 705 ICH enrolled in the China Stroke Center Alliance study. Patients were divided into four groups: underweight, normal weight, overweight and obese according to Asian-Pacific criteria. The primary outcome was in-hospital mortality. The secondary outcomes included non-routine discharge disposition and in-hospital complications. Discharge to graded II or III hospital, community hospital or rehabilitation facilities was considered non-routine disposition. Multivariable logistic regression analysed association of BMI with outcomes.Results 82 789 patients with ICH were included in the final analysis. Underweight (OR=2.057, 95% CI 1.193 to 3.550) patients had higher odds of in-hospital mortality than those with normal weight after adjusting for covariates, but no significant difference was observed for patients who were overweight or obese. No significant association was found between BMI and non-disposition. Underweight was associated with increased odds of several complications, including pneumonia (OR 1.343, 95% CI 1.138 to 1.584), poor swallow function (OR 1.351, 95% CI 1.122 to 1.628) and urinary tract infection (OR 1.532, 95% CI 1.064 to 2.204). Moreover, obese patients had higher odds of haematoma expansion (OR 1.326, 95% CI 1.168 to 1.504), deep vein thrombosis (OR 1.506, 95% CI 1.165 to 1.947) and gastrointestinal bleeding (OR 1.257, 95% CI 1.027 to 1.539).Conclusions In patients with ICH, being underweight was associated with increased in-hospital mortality. Being underweight and obese can both increased risk of in-hospital complications compared with having normal weight.